Prevalance and clinical characteristics of gingival recession in Greek young adults: A cross‐sectional study. Issue 5 (3rd May 2021) - Fragkioudakis, Ioannis; Tassou, Dimitra; Sideri, Maria; Vouros, Ioannis
Abstract: Objective: The current cross‐sectional study aimed to investigate the prevalence of gingival recession (REC) in a sample of young individuals. In addition, the association with several risk factors was examined. Materials & methods: A 104 subjects, aged 18–30 years old, were randomly enrolled in the study. Participants were requested to fill in a simple structured questionnaire in order to provide information on dental hygiene habits, educational level, smoking and history of orthodontic treatment. Afterwards, all the included individuals were subjected to a thorough clinical periodontal examination including gingival recession (REC), gingival biotype, plaque levels and gingival bleeding index (GBI) assessment. Results: The mean prevalence of REC in the studied population surpassed 50% with an equal distribution among females and males. The most common teeth associated with REC were the lower left canine and left 1st premolar. Among the examined variables, only the bleeding index was found to be associated with the presence of REC. Conclusions: Gingival recession was a prevalent condition among young individuals. Gingival inflammation was found to be the most significant factor affecting the incidence of REC.